Avifauna in silvopastoral systems in the Mesoamerican Biological Corridor, Tabasco, Mexico - González-Valdivia, Noel; Barba-Macías, Everardo; Hernández-Daumás, Salvador; Ochoa-Gaona, Susana (Revista de Biología Tropical, 2014)
Silvopastoral systems support local ecological and economical features as they enhance conservation of floral and faunal communities. As other animal communities, avifauna may be a good representative of habitat alterations, both as the species and functional levels. In order to attend the initiative of Mesoamerican Biological Corridor initiative (CBM) in the state of Tabasco, we studied the diversity of birds in two silvopastoral systems: scattered trees in pastures (ADP), and trees in boundary-hedgerows (AL). For this, we applied the fixed radius counting point method in three priority sites in Tabasco´s CBM during the dry and wet season of 2011, and a total of 56, 60 and 62 points were evaluated in Huimanguillo, Tenosique and Tacotalpa, respectively. We observed 2 084 individuals of 154 species (79-89% of expected diversity) and 36 bird families. We detected 92, 87 and 85 species in Huimanguillo, Tenosique and Tacotalpa, respectively, including 35 protected species, of which 23, 19 and 16 in each locality, respectively. All sites showed high diversity (H´≥3.20), low species dominance (D≥0.08) and high equitability (J≥0.77). Species composition showed differences between sites, being most similar Tacotalpa and Tenosique. Ten species were considered characteristic for sites. Although the silvopastoral system did contain protected species, the low diversity and the early successional character of the arboreal components were not attractive to frugivorous bird species. Diversification with native trees can improve the systems to create a complementary habitat and to increase landscape connectivity. The management of silvopastoral practices on cattle dominated landscapes in Tabasco could improve its ecological quality, and thus achieve the CBM´s objectives of biodiversity conservation combined with human economic activities.